Penatalaksanaan Fisioterapi Pada Subacromialis Bursitis Di Rst. Dr. Soedjono Magelang - Wahyuni, Dwi; , Agus Widodo, S.Fis, M.Kes (2016)
Background: Subacromialis Bursitis is an inflammation of the bursa (small sacs) are filled with synovial fluid excess and usually accompanied by pain and swelling between the rotator cuff and shoulder bones , known as the acromion. Objective: To investigate the benefit of using modalities such as Short Wave Diathermy (SWD), Transcutaneus Electrical Nerve Stimulation (TENS) and massage therapy can reducing pain, reducing oedema, increasing range of motion and increasing fungtional activity of shoulder sinistra. Result: The result obtained after the conducted therapy 6 times are as follow: silent pain: T0: 4,7 to T6: 2 , tenderness T0: 5,3 to T6: 2,5 and pain motion T0: 6,6 to T6:3,7. Reduncing oedem with didifference of acromion T0:1,5 to T6: 0, 5cm to medial T0: 3,6 to T6: 0,2, 10cm to medial T0: 1,3 to T6: 0,1. Increasing range of motion T0: S 50ͦ - 0ͦ - 80ͦ to T6: S 50ͦ -0ͦ - 155ͦ , T0: F 75ͦ -0ͦ - 15ͦ to T6: 165ͦ -0ͦ - 40ͦ , T0:- to T6: T 30ͦ -0ͦ - 120ͦ and T0: R(F90) 35ͦ-0ͦ -70ͦ to T6: R(F90)90ͦ -0ͦ -80ͦ. Increasing fungtional activity from T0:77,6% to T6:23,8%. Conclusion: Short Wave Diathermy (SWD), Transcutaneus Electrical Nerve Stimulation (TENS) and massage therapy can reducing pain, reducing oedema, increasing range of motion and increasing fungtional activity of shoulder sinistra Keywords: Subacromialis Bursitis, Short Wave Diathermy (SWD), Transcutaneus Electrical Nerve Stimulation (TENS) and massage therapy